Lucky in love - West, Kasie (Point, 2017)
"Maddie is a hard working high school senior, waiting to hear from the colleges she applied to, when on a whim she buys a lottery ticket and wins; suddenly she is the center of everybody's attention, including her struggling family, and not necessarily in a good way--only Seth Nguyen, her charming coworker at the local zoo, seems oblivious to her luck, and Maddie is not sure whether telling him will change their developing relationship"--Provided by publisher.